Cutaneous manifestations of diabetes mellitus: a clinico epidemiological study - Venkatesan, S.; Thamizhselvi, S.; ., Tharini (International Journal of Research in Dermatology, 2019)
Background: Diabetes mellitus is one of the commonest non communicable diseases seen all over the world, constituting 49% from India, i.e., 72 million patients according to the Indian Council of Medical Research. The aim of the study was to study the various skin manifestations in diabetic patients and to correlate them with glycemic levels. Methods: Patients for the study were chosen among those who were on treatment for diabetes mellitus and presented to the skin department with various cutaneous manifestations. Results: Infections were commonest cutaneous manifestations in both type 1 and type 2. Among infections, fungal infections were commoner followed by bacterial infections. Among house wives, the commoner was candidal dermatosis intertrigo-toe/finger cleft followed by chronic paronychia. Among bacterial infections, erythrasma was commonly followed by pyoderma. Among pyodermas, furunculosis was common. Most common associated dermatoses were acanthosis nigricans and acrochordons. Treatment-related manifestations were not found. Conclusions: In type 2 diabetic patients, infections were commonly followed by acanthosis nigricans, acrochordons, and generalized pruritus. Glycemic levels were higher in those with candidiasis and also with pyodermas.